Are sustainable funds doing the talk and the walk? An ESG score analysis of fund portfolio holdings - Martinez Meyers, Susana; Ferrero Ferrero, Idoya; Muñoz Torres, Maria Jesus (Elsevier Inc., 2024)
Our paper contributes to the growing literature by conducting a comparative analysis between sustainable funds (SF) and conventional funds (CF) with a global geographical perspective. The paper aims to test if SF are true to their identity through a comparative and multi-regional perspective analysis of the funds' ESG performance and sustainability risk. The sample comprises 92 matched pairs of funds. Our research shows that self-labeled sustainable funds exhibit better ESG performance and sustainability risk scores than their pairs,indicating alignment with their identity and nature. Furthermore,the results also indicate that there are different ESG behaviors depending on the geographical areas of investment. In particular,funds with portfolios invested in Europe present a higher ESG performance than those invested in North America,and funds invested in Emerging Markets and Asia present a lower performance and higher risk than those in North America. This paper provides three main novelties: 1) multiregional perspective,2) different ESG score perspectives using different and complementary indicators of sustainable behavior based on risk and performance,and 3) a matching process starting with the same fund management company,geographical area of investment and investment category that help us isolate the issue of the use of ESG labels. The results of this paper open new insights and research avenues that connect sustainable investment with aspects like quality of information,fiduciary duty,and regulatory development. © 2024 The Authors
Keywords: And greenwashing; ESG; ESG Score; Investment fund; SRI; Sustainable funds (SF); ODS 9 - Industria, innovación e infraestructura